2011
DOI: 10.1590/s1676-06032011000400013
|View full text |Cite
|
Sign up to set email alerts
|

Pollination biology and reproduction of Seemannia sylvatica (Kunth) Hanstein (Gesneriaceae) in the Serra da Bodoquena National Park, Mato Grosso do Sul

Abstract: Abstract:In Brazil, the family Gesneriaceae is represented by 23 genera and approximately 200 species. Seemannia sylvatica is an herb that occurs in dense populations in the riverbeds at Serra da Bodoquena. Goals of this study were to report the floral biology (on the first five days of anthesis), as well as to determine the breeding system and the pollinators of S. sylvatica. Data collection was conducted from June 2005 to July 2006 through monthly field trips, lasting for five days. Data on floral biology, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…A high number of thief/robber insects were recorded on S. elatior flowers. Even though this plant species is characterized as ornitophilous, this feature does not impede the occasional visits of different floral visitors, as observed by Camargo et al (2011) on flowers of Seemannia sylvatica (Kunth) Baill. (Gesneriaceae).…”
Section: Resultsmentioning
confidence: 91%
“…A high number of thief/robber insects were recorded on S. elatior flowers. Even though this plant species is characterized as ornitophilous, this feature does not impede the occasional visits of different floral visitors, as observed by Camargo et al (2011) on flowers of Seemannia sylvatica (Kunth) Baill. (Gesneriaceae).…”
Section: Resultsmentioning
confidence: 91%
“…Spontaneous self‐pollination is known in other Gesneriaceae but is rare within the family (see Fenster & Martén‐Rodríguez ; Camargo et al . ). Seed set was significantly higher in the autogamy treatment than in spontaneous‐pollinated flowers or flowers naturally visited by pollinators, which indicates that seed set in natural populations is pollen‐limited.…”
Section: Discussionmentioning
confidence: 97%
“…For example, high temperature and drought is the dominant factor for the growth of Cactus in the tropical grassland while air humidity is the main survival-limited factor for the growth of Rhododendron in the low altitude ground. Recent studies found that insect activity is related to the pollination traits (Kawakita, 2010;Camargo et al, 2011;Revel et al, 2012;Wiemer et al, 2012). Global climate change will seriously affect the flowering season and pollinator activity (Saetersdal and Birks, 1997;McCarty, 2001).…”
Section: Discussionmentioning
confidence: 99%